Gerak dan Laju Al-Jam’iyyatul Washliyah Cabang Cirebon (1957-2006) dalam Bidang Sosial-Keagamaan dan Pendidikan Islam - Zaenal Masduqi (IAIN Syekh Nurjati Cirebon, 2019)
AbstractMany young people who are active in Islamic mass organizations do not know the history and actions of these Islamic mass organizations and it is suspected that administratively many Islamic mass organizations that developed in the regions did not have a record of historical travel documentation. This is unfortunate for the organization's sustainability information in the midst of its activists. One of them is Al Washliyah, the writer as activist of Al Washliyah sees it as a emptiness and needs to be filled with written works related to Al Washliyah's activities in the Cirebon area. The method used to obtain data is the historical method which is packed with oral history. From this research, we can see the track record of Al Washliyah's actions which contains militancy and sacrificial spirit from all Al Washliyah activists from Medan who are actually preachers and clerics as well as Cirebon figures who are actually Agniya, educators, community leaders and government. They are united in realizing the dharma of their devotion to the people and nation through the Al Washliyah Islamic movement. Keywords: Al Washliyah, militancy, Islamic education, da'wah and social